Remodeling Tulang Sukses Klinis Saat Autotransplantasi Gigi Disertai Penambahan Bahan Cangkok Tulang - Heru Maksmara (Jurnal Material Kedokteran Gigi, 2013)
The primary goal of periodontal treatment is regeneration of the supporting periodontal structures: i.e., formation of new bone, cementum, and new periodontal ligament collagen fibers. Successful using bone graft are many reported as bone replacement material promoting new bone formation, remodeling. Periodontal regeneration may be achieved by migration into periodontal defects and proliferation and differentiation of periodontal cells. Implementation. 14 year old young boy got trauma in his anterior upper jaw. Extra oral examination he got brushess of upper lip and bledding. Panoramic view shows bone fracture. His teeth of 21 and 22 got lost conections with bone, tooth mobility 40, lost clinical attachment of gingiva and palatal mucosa, and 8 - 12 mm of probing depth. Patients who experience head trauma around face, want to keep teeth in place as before, and do not require the use of prostheses. Teeth which are detached from the socket and experience shakiness 40 in extraction and cleaned using saline solution, and got a root canal treatment. Areas of trauma also be cleaned with saline solution and arranged the bone fragments. For bone remodeling, bone graft material may be used; demineralized freeze-dried bone allograft (DFDBA). Teeth in reimplantation must be splinted well. Patients should have good oral hygiene and do not consume food in the form of dense and chewy, and obey the traffic control. The success is determined by the parameters of probing depth, shakiness tooth, bleeding on probing, clinical attachment level, data taken before surgery and after six months of operation, if it is necessary, re-do the operation anyway. Results. After sixth month operation. There is no bleeding on probing and dental shakiness after six months of operation, and decreasing of probing depth of 10-15 mm to 3-4 mm. After 9 month of splint can be off. Conclusions. With all the limitations of experience, in this research can be concluded that we can maintain post-traumatic tooth in place of autotransplants technique by the periodontal tissue remodeling technique by using the additional of DFDBA bone graft material.